2006
DOI: 10.1634/stemcells.2005-0380
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Functional Cardiomyocytes from Rhesus Monkey Embryonic Stem Cells

Abstract: Embryonic stem cells (ESCs) from mice and humans (hESCs) have been shown to be able to efficiently differentiate toward cardiomyocytes (CMs). Because murineESCs and hESCs do not allow for establishment of preclinical allogeneic transplantation models, the aim of our study was to generate functional CMs from rhesus monkey ESCs (rESCs). Although formation of ectodermal and neuronal/glial cells appears to be the default pathway of the rESC line R366.4, we were able to change this commitment and to direct generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Interestingly, RT-PCR analyses revealed that both the undifferentiated iPS cells and the ES cells expressed significant amounts of mRNA for the mesodermal markers Brachyury and Mesp1 and for cardiac markers including the MLC (Figure 3). Similar results have been reported for both human and rhesus monkey ES cells 26,27 and are consistent with the reports that undifferentiated ES cell cultures often contain some colonies with a "differentiated" morphology. 27 Further RT-PCR analyses detected expression of the marker genes typical for mesoderm, endoderm, cardiac mesoderm, and cardiomyocytes in the differentiating iPS cells (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, RT-PCR analyses revealed that both the undifferentiated iPS cells and the ES cells expressed significant amounts of mRNA for the mesodermal markers Brachyury and Mesp1 and for cardiac markers including the MLC (Figure 3). Similar results have been reported for both human and rhesus monkey ES cells 26,27 and are consistent with the reports that undifferentiated ES cell cultures often contain some colonies with a "differentiated" morphology. 27 Further RT-PCR analyses detected expression of the marker genes typical for mesoderm, endoderm, cardiac mesoderm, and cardiomyocytes in the differentiating iPS cells (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…With this in mind, the ideal cell source for cardiac tissue engineering would be patient-specific stem cell-derived cardiomyocytes. Cardiac 1 differentiation has been demonstrated successfully for both embryonic stem cells 5,6 and induced pluripotent stem cells [7][8][9][10] from various species; however, these cells are currently not suitable for clinical application in patients due to the methods used in their generation. Despite recent promising results regarding scalable expansion 11,12 and differentiation 13 of embryonic and pluripotent stem cells, the available numbers of stem cell-derived cardiac cells have not been sufficient for the generation of BCT of appropriate sizes for therapeutic application so far.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the prominent role of Ca 2+ as a cellular second messenger in directing the fate of stem cells towards cardiac [19][20][21]. We postulated that one of the critical targets f o r i n d u c t i o n o f [ C a 2 + ] i s i g n a l i n g i n v o l v e d i n cardiomyogenesis could be the activation of purinergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular [Ca +2 ] i exerts multiple functions in the process of cardiac cell differentiation and early heart development depending upon the amplitude, space, and time of [Ca 2+ ] i signaling. Decoding the molecular mechanism of the multifaceted roles of [Ca 2+ ] i signaling will therefore not only contribute to decipher molecular pathways of cardiogenesis but also help to elaborate protocols for highly efficient cardiomyocyte differentiation from ES cells [18][19][20][21]. During embryonic heart formation, a couple of cardiogenic factors turn on Ca 2+ -dependent signaling pathways in cardiac progenitor cells.…”
Section: Introductionmentioning
confidence: 99%